PERTANGGUNGJAWABAN PELAKU USAHA PEMBERI DISKON PALSU DALAM PRAKTIK JUAL BELI EVENT TANGGAL KEMBAR E-COMMERCE - Salwa Noviana Putri (Warmadewa University Press, 2023)
E-commerce is most used by people because its efficiency and attractive discounts, so the government provides legal protection through Consumer Protection Act to limit the actions of sellers to avoid losses to consumers because there are still many fake discounts given by sellers at twin date events. The research aims to determine responsibility of sellers who give fake discount promotions and to find out the solutions provided. Normative juridical research method used to examine legal norms and relate them to the problems raised by conducting a literature study of related legislation and legal regulations, books, scientific articles, and dictionaries which will be analyzed with real cases that occurred in Indonesia. The research shows there is ignorance of the law by sellers cause no responsibility given for providing fake discounts where sellers should be legally obliged to convey information that is accurate due to the lack of public knowledge regarding the existence of legal regulations. The research recommends that the government needs to be more assertive in enforcing existing legal regulations by closing the accounts of sellers who give fake discounts or updating regulations containing a prohibition on running a business within a certain period of time for business actors who give fake discounts and requiring all e-commerce platforms to include legal rules regarding sales via e- commerce to sellers before creating an account to carry out sales activities to provide a deterrent effect and provide legal education for the public through seminars or social media.